Antimicrobial resistance and molecular genotyping of Escherichia coli and Staphylococcus aureus isolated from some Egyptian cheeses - Kasem, Nahed Gomaa; Ashmawy, Maha Al; Elsherbini, Mohammed; Abdelkhalek, Adel (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This work investigated the antimicrobial resistance (AMR) and virulence of Escherichia coli and Staphylococcus aureus in communally consumed cheeses in Egypt. Materials and Methods: This study examined 100 samples of Domiati, Tallaga, Cheddar, and Ras cheese collected from several shops and supermarkets. Samples were spread on selective media to isolate bacterial strains. Molecular characterization of bacterial isolates was carried out using polymerase chain reaction to determine Shiga toxin 1 (stx1), Shiga toxin 2 (stx2), eaeA, and nuc genes. The isolates were tested for susceptibility to 14 antibiotics by disk diffusion assay. Results: In this study, several E. coli serotypes were identified. E. coli O26:H11, O103:H2, and O111:H2 expressed stx1/2, E. coli O114:H4 expressed stx1, E. coli O17:H18, O21:H7 and O146:H21 expressed stx2, while only E. coli O26:H11 and O111:H2 expressed eaeA. The E. coli isolates were resistant to at least one antibiotic, while most isolates (82.4%) showed multidrug resistance (MDR). AMR to erythromycin was the highest (100%), followed by nalidixic acid (94.1%), cefotaxime (82.4%), vancomycin and cephalothin (64.7%), penicillin G (52.9%), sulfamethoxazole (47.1%), amikacin and kanamycin (35.3%), ampicillin (29.4%), tetracycline and ciprofloxacin (23.5%), and doxycycline (11.8%), while gentamicin showed the least resistance (5.9%). The multiple antibiotic resistance (MAR) index of the isolated E. coli ranged from 0.071 to 1 (mean = 0.478). All S. aureus isolates expressed the nuc gene and demonstrated resistance to at least one antibiotic, and 90% of isolates were MDR. AMR to kanamycin and cephalothin was the highest (100%), followed by penicillin (90%), doxycycline (70%), nalidixic acid and sulfamethoxazole (60%), erythromycin (50%), tetracycline, cefotaxime, and gentamicin (40%), ciprofloxacin and ampicillin (30%), and amikacin (20%). In comparison, vancomycin showed the least resistance (10%). MAR index of isolated S. aureus ranged from 0.143 to 1 (mean = 0.529). Conclusion: The antimicrobial-resistant E. coli and S. aureus are potential risks for public health and may have a role in disseminating AMR to other pathogenic and non-pathogenic microbes. J. Adv. Vet. Anim. Res., 8(2): 246-255, June 2021